Permanent education process in the daily routine of primary health care (Research, Society and Development, 2020)
The objective of this study is to demonstrate how permanent health education has been developing within the daily routine of primary health care in a municipality in Pará-Brazil. This is a single holistic, explanatory, descriptive case of study with a qualitative approach. Data collection was carried out through a focused interview with 43 health professionals. For the analysis, we used an analytical grounded theory procedure. From this analysis emerged the category of Permanent Health Education Process experienced in daily work and the Demands subcategories of actions to be developed; Elaboration of the Permanent Health Education Project; Development of Permanent Health Education actions; and Evaluation of Permanent Education in Health actions. The development of permanent education is within  the implementation phase, a vertical and centralized management process has become evident, with a predominance of traditional educational processes, information transfer, and a restricted critical reflection process of reality.